2019
DOI: 10.1016/j.arabjc.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the bentonite filler on structure and properties of composites based on hydroxyethyl cellulose

Abstract: Effect of the bentonite filler on structure and properties of composites based on hydroxyethyl cellulose, Arabian Journal of Chemistry (2015), doi: http://dx. AbstractGranulometric test and morphological analysis of the bentonite particles were performed using laser diffraction and low-temperature nitrogen adsorption-desorption techniques. Bentonite particles were immobilized into the hydroxyethyl cellulose matrix by mechanical dispersion, and composite films were obtained. The effect of concentration of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Grading and porosity of bentonite were studied by us previously using N 2 adsorption–desorption and laser diffraction techniques (Alekseeva et al 2019a ). It was found that the particle diameter of bentonite did not exceed 14 μm; the particle-size distribution was mono-modal with peak near 5.6 μm.…”
Section: Resultsmentioning
confidence: 99%
“…Grading and porosity of bentonite were studied by us previously using N 2 adsorption–desorption and laser diffraction techniques (Alekseeva et al 2019a ). It was found that the particle diameter of bentonite did not exceed 14 μm; the particle-size distribution was mono-modal with peak near 5.6 μm.…”
Section: Resultsmentioning
confidence: 99%
“…23 The formation of Ni 2 O 3 H phase could be due to the role of oxidization agent as it partially hydrolyzed nickel oxide (NiO x ) for the catalytic process. 55 The diffraction peak at 2θ = 6.3°might be due to the inherent presence of montmorillonite (MMT) 56,57 in the cotton cellulose, and the same has been suppressed after the modification of cotton surface with NiO x . The major peak found at 22.2°with an increased intensity and decreased full width at half-maximum might be due to the increase in crystallite size with secondary wall cellulose.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, in films filled with 3 wt.% of organobentonite, good dispersion of filler particles in HEC matrix can be observed, but also agglomerates with varying size are noticed ( Figure 5(b)). Figure 6 shows the X-ray diffraction patterns of organobentonite and bentonite (reported previously [24]). The XRD pattern of bentonite (a) contains a wellpronounced reflection at 2 = 7 ∘ , which corresponds to a distance between aluminosilicate basal surfaces of 1.26 nm.…”
Section: Surface Morphologymentioning
confidence: 99%
“…Previously in [24], we reported on researches the porous structure of bentonite. The results are shown in Figures 3(c) and 3(d).…”
Section: Porous Structurementioning
confidence: 99%
See 1 more Smart Citation